1999
DOI: 10.1515/jpm.1999.035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of delayed absorbable suture v nonabsorbable suture for treatment of incompetent cervix

Abstract: Based on our findings delayed absorbable suture material may be a reasonable alternative during cerclage placement, with the added benefit of spontaneous degradation versus surgical removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…These include human fascia lata [1], sutures such as Mersilene ™ (Ethicon, NJ) (2), silk, Prolene ™ (Ethicon, NJ), Tevdek ™ (Teleflex, PA), metal wire, as well as Mersilene tape ™ (Ethicon, NJ), and others [5–7,9]. Today, most commonly used ones are Mersilene 5mm tape ™ (Thicon RS-21 or D-8113; Ethicon, NJ) [8,10–13] and large nonabsorbable monofilament (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include human fascia lata [1], sutures such as Mersilene ™ (Ethicon, NJ) (2), silk, Prolene ™ (Ethicon, NJ), Tevdek ™ (Teleflex, PA), metal wire, as well as Mersilene tape ™ (Ethicon, NJ), and others [5–7,9]. Today, most commonly used ones are Mersilene 5mm tape ™ (Thicon RS-21 or D-8113; Ethicon, NJ) [8,10–13] and large nonabsorbable monofilament (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Another small retrospective study found braided suture to be associated with decreased PTB < 28weeks and improved neonatal survival compared to Mersilene tape ™ [6]. In a small study which included women undergoing either history- or physical exam-indicated McDonald cerclage, gestational age at delivery and interval from cerclage to birth were similar in women who received a Mersilene tape ™ vs those who received a Prolene ™ suture [7]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No prospective studies have been performed to compare suture type in this setting, however retrospective data suggest similar outcomes regardless of suture. 38 Results from a secondary analysis from the Expectant Management compared with Physical Examination-indicated Cerclage study presented in abstract form at the 27th annual meeting of the Society of Maternal Fetal Medicine in San Francisco, CA suggested improved outcomes with use of braided suture when compared with Mersilene tape. 39 Advocates of Mersilene tape cite stronger circumferential support with this suture when compared with monofilament suture.…”
Section: Shirodkar Versus Mcdonaldmentioning
confidence: 99%
“…Vincenzo Berghella 34 conducted a study to assess whether type of suture material affects cerclage efficacy for preterm birth prevention and they concluded that type of suture material may not affect ultrasound-indicated cerclage efficacy in high-risk women with short CL, but further study is needed. Y. E. Abdelhak 35 compared the efficacy of traditional non absorbable suture to delayed absorbable suture for used in McDonald cervical cerclage. They conducted a retrospective analysis of all cerclage procedures over a one year interval and stratified by the type of suture material.…”
mentioning
confidence: 99%